1989
DOI: 10.1103/physrevlett.62.2825
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in flowing sand

Abstract: Using digital subtraction radiography, we study the basic modes of a granular material (here sand) flowing through a flat hopper. These modes take the form of density waves whose formation and propagation is controlled by several parameters, including the mass flow rate M and the hopper angle 0. We consider the effect of roughness on pattern formation in this system using mixtures of smooth and faceted sand and show the existence of a bifurcation at a mass fraction of faceted sand Xz& 0.2. Propagating patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(109 citation statements)
references
References 11 publications
7
101
0
1
Order By: Relevance
“…Baxter et al found density waves in a hopper only if a certain amount of rough sands is mixed with smooth sands [28]. The role of the rough sands is not clearly established.…”
Section: Density Waves In Hoppersmentioning
confidence: 99%
“…Baxter et al found density waves in a hopper only if a certain amount of rough sands is mixed with smooth sands [28]. The role of the rough sands is not clearly established.…”
Section: Density Waves In Hoppersmentioning
confidence: 99%
“…larger velocity above the orifice than near the stagnant region), as suggested by the shape of some experimental density waves (Baxter et al, 1989). The geometrical spot propagator, P s (x, |z, x 0 , z 0 ), is the conditional probability of finding a spot at horizontal position x once it has risen to a height z from an initial position (x 0 , z 0 ).…”
Section: Statistical Dynamics Of Spotsmentioning
confidence: 99%
“…Beverloo thoroughly investigated the relation between the orifice size and the mass flow rate in cylindrical silos and proposed a formula describing the observed dependence [6]. Using radiography, Baxter, et al observed the density wave in the hopper flow and showed various patterns of the wave depending on the particle roughness and the hopper angle [7].…”
Section: Introductionmentioning
confidence: 99%